2018
DOI: 10.1002/mrm.27165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anesthesia on renal function and metabolism in rats assessed by hyperpolarized MRI

Abstract: This study demonstrates different renal metabolic and hemodynamic changes under 3 different anesthetics, using hyperpolarized MR in rats. Inactin and sevoflurane were found to affect the renal hemodynamic and metabolic status to a lesser degree than FFM. Sevoflurane anesthesia is particularly easy to induce and maintain during the whole anesthesia procedure, and as such, represents a good alternative to inaction, although it alters the blood glucose level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
(77 reference statements)
0
12
1
Order By: Relevance
“…However, we note that previous work has reported that the lactate to pyruvate ratio is decreased under isoflurane anaesthesia of increasing depth in the brain 100 , heart 101 , and kidney 102 . Additionally, the lactate to pyruvate ratio is altered profoundly following the administration of different anaesthetic agents, with a reduction in the derived metabolic rate constant with increasing depth of anaesthesia from alpha-chloralose to pentobarbital 103 .…”
Section: Discussioncontrasting
confidence: 44%
“…However, we note that previous work has reported that the lactate to pyruvate ratio is decreased under isoflurane anaesthesia of increasing depth in the brain 100 , heart 101 , and kidney 102 . Additionally, the lactate to pyruvate ratio is altered profoundly following the administration of different anaesthetic agents, with a reduction in the derived metabolic rate constant with increasing depth of anaesthesia from alpha-chloralose to pentobarbital 103 .…”
Section: Discussioncontrasting
confidence: 44%
“…The main limitation of this study is the necessity for anesthesia in animal studies, which may alter metabolic measurements . Propofol has been reported to induce transient hyperglycemia in pigs and insulin resistance in rats, and although no data on pigs exist on this, it is possible that the prolonged effect of feeding is the result of the anesthesia used.…”
Section: Discussionmentioning
confidence: 97%
“…The main limitation of this study is the necessity for anesthesia in animal studies, which may alter metabolic measurements. 48 Propofol has been reported to induce transient hyperglycemia in pigs 49 and insulin resistance in rats, 50 and although no data on pigs exist on this, it is possible that the prolonged effect of feeding is the result of the anesthesia used. As such, these results may not be directly translated into human trials, and further research is needed in order to clarify whether the effects of feeding can be replicated in nonanesthetized humans.…”
Section: Study Limitations and Disadvantages Of The Modelmentioning
confidence: 99%
“…It is also associated with hyperthermia and muscle weakness, postoperatively (Maeda, Iranami, & Hatano, 1997). Qi et al (2018) compared the effects of various anesthesia and found that sevoflurane decreases the levels of sodium and insulin, whereas, it suggestively, increases the blood sugar level. Metabolism of sevoflurane in the presence of soda lime, giving compound A (fluoromethyl-2,2 difluoro-1-[trifluoromethyl] vinyl ether; Frink et al, 1992) is found to have nephrotoxic effects, as a consequence of glutathione and cysteine metabolites (Jin, Baillie, Davis, & Kharasch, 1995).…”
Section: Halogenated Anesthesiamentioning
confidence: 99%